2019
DOI: 10.3390/molecules24162901
|View full text |Cite
|
Sign up to set email alerts
|

Cordycepin Isolated from Cordyceps militaris: Its Newly Discovered Herbicidal Property and Potential Plant-Based Novel Alternative to Glyphosate

Abstract: There is currently much interest in finding new phytochemicals among plants and fungi as nature-based alternatives to replace problematic herbicides such as glyphosate, which are preferentially used in agricultural production n. We discovered striking herbicidal potency in Cordyceps militaris (L.) and identified cordycepin as its principal plant growth inhibitor. Cordycepin obtained as an ethyl acetate extract was subjected to column chromatography and evaluated for its bioassay-guided phytotoxic capacity agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 50 publications
(71 reference statements)
1
29
0
2
Order By: Relevance
“…Therefore, cordycepin, phenolics, and flavonoids were polar compounds extracted well using a polar solvent. The results were well in accordance with Quy et al (2019), who reported that solvent polarity and extraction time affected the cordycepin content of C. militaris fruiting body [36]. Besides, Abarca-Vargas et al (2016) reported that phenolic compounds were more efficiently extracted by high polar solvents and the total phenolic content is obviously related to type of solvent and its polarity index [37].…”
Section: Chemical Composition Of C Militaris Extractssupporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, cordycepin, phenolics, and flavonoids were polar compounds extracted well using a polar solvent. The results were well in accordance with Quy et al (2019), who reported that solvent polarity and extraction time affected the cordycepin content of C. militaris fruiting body [36]. Besides, Abarca-Vargas et al (2016) reported that phenolic compounds were more efficiently extracted by high polar solvents and the total phenolic content is obviously related to type of solvent and its polarity index [37].…”
Section: Chemical Composition Of C Militaris Extractssupporting
confidence: 88%
“…Additionally, polysaccharide fractions containing t-Galp and 1,2-Manp have been reported for a potent FRAP value of 78.4 µmol Fe 2+ /g [53]. Similarly, cordycepin was not responsible for lipid peroxidation inhibitory activity of C. militaris extract (R 2 = 0.1914) since hydrophilicity of cordycepin was incompatible with the lipid peroxidation assay [36,54]. On the other hand, chemical components of C. militaris extract responsible for high ferric reducing antioxidant power were other compounds than cordycepin because there was almost no relation between the cordycepin content and ferric reducing ability (R 2 = 0.0657).…”
Section: Antioxidant Activities Of C Militaris Extractsmentioning
confidence: 99%
“…Cordycepin is an important metabolite in C. militaris , and possesses the potential as a medicine, food and herbicide [79] , [80] , [81] . In T. guangdongense , extremely low levels of cordycepin were detected, and the genes involved in cordycepin biosynthesis were not identified in the genome of T. guangdongense .…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of an E. variecolor-derived sponge (Cinachyrella sp.) led to the isolation of 7 new polyketides: varioxiranols A−G (117−123) and a new hybrid polyketide synthase (PKS)-isoprenoid metabolite, 19-O-methyl-22-methoxypre-shamixanthone (124) (Figures 7 and 8). Varioxiranols F and G were reported as the first metabolites that include a link of xanthone moiety to a benzyl alcohol via an ether bond [72].…”
Section: Meroterpenesmentioning
confidence: 99%
“…Based on the scientific literature published on the genus Emericella and some other fungal species [124][125][126][127][128], fungal metabolites could replace some conventional shelf drugs that are common in the market with extremely few drawbacks, for example cordycepin (a nucleoside obtained from Cordyceps militaris) replaces glyophosate and benzoic acid. Cordycepin showed a maximum inhibition on the germination and growth of Raphanus sativus (radish) (IC 50 = 0.052-0.078 mg/mL).…”
Section: Conclusion and Future Prospectivementioning
confidence: 99%